Analisis Pengaruh Kualitas Pelayanan Kesehatan Terhadap Kepuasan Pasien Di Rumah Sakit Umum Daerah Kabupaten Karanganyar - Fajri, Imam Khoirul; , Dr. dr. H. Iwan Setiawan A, Sp. THT-KL; , Drs. M Farid Wajdi, M.M, Ph.D (2016)
The services sector is a rapidly growing area in the world economy and the health service is the organization that plays an important role in it's growth. This study aimed to analyze the dimensions of health care quality does affect the level of patient satisfaction in Regional General Hospital of Karanganyar. This study was an observational analytic study with cross-sectional approach. The population in this study was all patients in Regional General Hospital of Karanganyar, both outpatient and inpatient. Samples were determined by simple random sampling technique, with respondents as many as 110 people. Methods of data collection techniques used are questionnaire. Data analysis method used is multiple linear analysis method. The research results obtained by using SPSS, t-test results showed that reliability and assurance variable did not have a significant effect on patient satisfaction, but tangible, responsiveness, and empathy variable have a significant effect on patient satisfaction. At the same time the F-test showed that tangible, reliability, responsiveness, assurance, and empathy variable simultaneously have a significant influence on patient satisfaction.